2016
DOI: 10.3390/rs8080614
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Sensing and Digital Terrain Models Applied to Digital Soil Mapping and Modeling of Brazilian Latosols (Oxisols)

Abstract: Digital terrain models (DTM) have been used in soil mapping worldwide. When using such models, improved predictions are often attained with the input of extra variables provided by the use of proximal sensors, such as magnetometers and portable X-ray fluorescence scanners (pXRF). This work aimed to evaluate the efficiency of such tools for mapping soil classes and properties in tropical conditions. Soils were classified and sampled at 39 locations in a regular-grid design with a 200-m distance between samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 80 publications
1
24
0
1
Order By: Relevance
“…In addition, by providing results quickly and inexpensively, it may favor gathering more observations (points visited) in the field and also, through predictions, reduce the number of laboratory analyses. The use of pXRF to improve spatial and non-spatial soil predictions was also found by Silva et al (2016b), who used magnetic susceptibility and pXRF data, as well as continuous variables derived from digital elevation model for soil classes and properties prediction in Brazil, finding that magnetic susceptibility and pXRF data increased the models accuracy when associated with terrain data. Weindorf; Bakr; Zhu (2014), after presenting examples of correlations among the element contents obtained by pXRF and results of laboratory analysis, suggested that many works using this equipment would be performed focusing on predicting soil properties in the years to come.…”
Section: Order Of Importancementioning
confidence: 95%
See 2 more Smart Citations
“…In addition, by providing results quickly and inexpensively, it may favor gathering more observations (points visited) in the field and also, through predictions, reduce the number of laboratory analyses. The use of pXRF to improve spatial and non-spatial soil predictions was also found by Silva et al (2016b), who used magnetic susceptibility and pXRF data, as well as continuous variables derived from digital elevation model for soil classes and properties prediction in Brazil, finding that magnetic susceptibility and pXRF data increased the models accuracy when associated with terrain data. Weindorf; Bakr; Zhu (2014), after presenting examples of correlations among the element contents obtained by pXRF and results of laboratory analysis, suggested that many works using this equipment would be performed focusing on predicting soil properties in the years to come.…”
Section: Order Of Importancementioning
confidence: 95%
“…This procedure aimed to evaluate the possibility of using pXRF data as a basis for mapping soil properties (Duda et al, 2017;Silva et al, 2016b), providing easily obtainable variables, at low cost, rapidly and with no generation of chemical residues.…”
Section: Spatial Prediction Of Soil Properties From Pxrf Datamentioning
confidence: 99%
See 1 more Smart Citation
“…These authors found a significant correlation between Fe and clay content (R 2 = 0.94) in soils of the state of Louisiana (USA). This relationship was also found in Latosols, highly weathered tropical soils, developed from gabbro and gneiss, in Minas Gerais State, Brazil, for sand and clay contents using ordinary least square multiple linear regression (Silva et al, 2016). Weindorf et al (2013) satisfactorily determined the calcium sulphate content in soils using pXRF.…”
Section: Agronomic Applicationsmentioning
confidence: 93%
“…Regarding soil survey, classification and digital mapping perspectives, Silva et al (2016) employed pXRF elemental data in addition to soil magnetic susceptibility and high resolution digital terrain models (slope gradient, topographic wetness index, etc.) to aid in distinguishing four types of Latosols (Oxisols) according to their chemical properties related to parent material, and mapping their spatial distribution over the study area, in Minas Gerais (Brazil).…”
Section: Pedological Applicationsmentioning
confidence: 99%